Comparative Study of Organoleptic Quality and Use Test of Pasteurized, Freeze-dried and Hot Airdried Quail Eggs Produced in Benin - EKPO, JUSTIN; EDIKOU, Koba Ulrich Spéro; ATCHOUKE, Laurent G. D.; DOSSOU, JOSEPH (My University, 2022)
This study aimed to evaluate the organoleptic quality and to carry out a use test of pasteurized, freeze-dried and hot air-dried quail eggs in order to compare with normal liquid quail and hen eggs. These egg products were reconstituted and omelets prepared using each quail egg product and the controls. Freezedried, hot air-dried quail eggs were mixed differently with 1% corn porridges. Single porridge served as the control. Each product type was subjected to a single round of testing by a panel of 30 untrained individuals. Reconstituted hot air-dried eggs were different (p ˂ 0.05) from reconstituted pasteurized and freeze-dried, liquid quail and hen eggs for all organoleptic parameters. While liquid, pasteurized quail eggs and liquid hen egg omelets differed (p ˂ 0.05) from freeze-dried quail egg and hot air-dried quail egg omelets. The single porridge was different (p ˂ 0.05) from freeze-dried and hot air-dried quail egg porridges.
Keywords: Freeze-dried quail egg omelets; hot air-dried quail egg porridges; reconstituted pasteurized quail egg